Antioxidant Activity Test of Red Spinach’s Extract (Blitum rubrum) in Ethanol Solvent and Water Solvent with DPPH - Nur A. O. Buhang; Siti Nuryanti; Daud K. Walanda (Universitas Tadulako, 2019)
The study of red spinach antioxidants (Blitum rubrum) in two types of solvents i.e ethanol and water has been performed. The purpose of this study was to determine the antioxidant activity of red spinach extract from Tinombo Selatan district, Central Sulawesi. Red spinach was macerated in ethanol and water to obtain variations of extract concentrations of 20, 40, 60, and 80 mg/L. Free radicals used were DPPH reagents while vitamin C was used as a positive control. The measurement of absorbance of red spinach’s extract was conducted by spectrophotometric. The results showed that IC50 extract of red spinach in ethanol and water were 51.404 mg/L and 52.227 mg/L, while the value of IC50 vitamin C in ethanol and water solvent was 43.241 mg/L and 140.507 mg/L. Based on the IC50 red spinach’s extract in ethanol and water have strong antioxidant activity.